Keepers of the flame C.S. McWilliams - McWilliams, C.S. (Cimarron, New Mexico Cimarron Legend, 2023)
Article on the Cimarron Fire Department and the firework display and the process of raising money.
Master List item # 104
File location is in the Raton File Cabinet
Keywords: Espinoza, Joe; Doerr, Billy; Carter, Eddie; Martinez, Leo; Paiz, Lino; Archuleta, Larry; Gurule, Richard; Hollis, Jim; Jeffers, Casey; LeDoux, Ernie; Martinez, Anthony; Martinez, George; Martinez, John R; Matinez, Kenny; Martinez, Fred; Martinez, Mario; Martinez, Tim; Martinez, Gilbert; Potter, James; Zamora, Gilbert; Martinez, Jerry; Cimarron Volunteer Fire Department; Mavericks Club; Fire Department; Volunteer; Fireworks; Display; Donations; Fundraising; Family; Recognition; Education; Cimarron, New Mexico